PELATIHAN PENGARSIPAN SECARA ELEKTRONIK (E-FILLING) BAGI PERANGKAT DESA DI PEKON SUKANEGERI JAYA - Dedi Darwis; Heni Sulistiani; Auliya Rahman Isnain; Ikbal Yasin; Fikri Hamidy; Rika Mersita; Elvano Delisa Mega (Universitas Teknokrat Indonesia, 2022)
This service activity in the form of electronic archiving training or e-filling is motivated by archiving activities carried out at the village office still using the traditional way, namely using paper. This method will cause many problems, so it is necessary to conduct electronic archiving training for village officials. The village office in Pekon Sukanegeri Jaya has been equipped with computer equipment and an internet network that can be used for electronic archive management. However, the skills and knowledge of village officials are still lacking, especially for archiving using Google Drive media. The purpose of implementing this service is that with the existence of electronic archiving training for village officials, it is hoped that archive management at the village office can be more organized and make it easier for village officials to re-search the archive files needed at any time.